2021
DOI: 10.3390/electronics10131605
|View full text |Cite
|
Sign up to set email alerts
|

An Informative Path Planner for a Swarm of ASVs Based on an Enhanced PSO with Gaussian Surrogate Model Components Intended for Water Monitoring Applications

Abstract: Controlling the water quality of water supplies has always been a critical challenge, and water resource monitoring has become a need in recent years. Manual monitoring is not recommended in the case of large water surfaces for a variety of reasons, including expense and time consumption. In the last few years, researchers have proposed the use of autonomous vehicles for monitoring tasks. Fleets or swarms of vehicles can be deployed to conduct water resource explorations by using path planning techniques to gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The utilization of ASVs is an increasingly common option for autonomous operation in hydrological resources and harbors [6,[16][17][18][19][20][21]. Applications range from bathymetry surveys [16], pollutant modeling and monitoring [17], or patrolling for early warning .…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of ASVs is an increasingly common option for autonomous operation in hydrological resources and harbors [6,[16][17][18][19][20][21]. Applications range from bathymetry surveys [16], pollutant modeling and monitoring [17], or patrolling for early warning .…”
Section: Previous Workmentioning
confidence: 99%
“…Applications range from bathymetry surveys [16], pollutant modeling and monitoring [17], or patrolling for early warning . In most applications, Artificial Intelligence or metaheuristic optimization techniques are usually applied to solve complex NP-hard problems: Bayesian optimization [18], genetic algorithms (GA) [19], Swarm Intelligence [20], or DRL [21].…”
Section: Previous Workmentioning
confidence: 99%
“…The utilization of ASVs is an increasingly common option for autonomous operation in hydrological resources and harbors [16,17,6,18,15,19,20]. Applications range from bathymetry surveys [16], pollutant modeling and monitoring [17], or patrolling for early warning .…”
Section: Previous Workmentioning
confidence: 99%
“…Applications range from bathymetry surveys [16], pollutant modeling and monitoring [17], or patrolling for early warning . In most applications, Artificial Intelligence or metaheuristic optimization techniques are usually applied to solve complex NP-hard problems: Bayesian optimization [18], genetic algorithms (GA) [15], Swarm Intelligence [19], or DRL [20].…”
Section: Previous Workmentioning
confidence: 99%
“…We propose a Multi-objective Particle Swarm Optimization (PSO) technique designed for an heterogeneous fleet of ASVs. The PSO algorithm was chosen based on a comparative study conducted in [14],where various Swarm Intelligence (SI) algorithms were evaluated. The results of this comparison indicated that PSO offers several advantages for monitoring application.…”
Section: Introductionmentioning
confidence: 99%